Modelo multicritério para apoio à tomada de decisão baseado em avaliação do ciclo de vida e indicadores corporativos - Piekarski, Cassiano Moro (2015)
Life Cycle Assessment (LCA) allows identify opportunities to improve environmental performance, providing knowledge about products and processes and supporting decision-making in order to achieve advantages. Decision-making based on LCA results involves, in addition to the environmental aspects and impacts, others important criteria. In this sense, this thesis aimed to develop a multi-criteria model for decision-making based on life cycle assessment and corporate indicators. The model developed has interactive nature and can be generalized. The model was validated using data for different scenarios of MDF panel production life cycle. The pairwise model evaluates the options for different scenarios and identifies the most attractive option in accordance with a final index. The final index is composed of specific, sub-dimensions and indicators. The environmental dimension is based on an LCA, which was modeled in Umberto software and used Eco-Invent 2.2 as database. For the model structure and construction of cardinal scale was used MACBETH method using M-MACBETH software. The model validation was made by evaluation of three decision-making scenarios in MDF panel production (changes in production processes, changes in process parameters and changes in product thickness variations). The results allowed to reach academic advances in order to support decision models structures based on LCA and multi-criteria. The results allowed interpreting and generating knowledge about production process, product life cycle and industrial management. In this sense, it is concluded that the model is able to support and generate knowledge on decision-making processes based on LCA and other corporate indicators.